Analysis of Operational Planning in Increasing the Number of Umrah Pilgrims at PT Asyesa Hasanah Tour & Travel Padang City - Mita Kalsum; Khadijah Nurani (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2023)
This study aims to determine the operational planning of PT Asyesa Hasanah Tour & Travel SUMBAR Padang City and to find out what are the inhibiting factors for the operational planning of PT Asyesa Hasanah Tour & Travel SUMBAR Padang City in increasing the interest of Umrah pilgrims after the Covid-19 pandemic. This research is a descriptive qualitative research by choosing. The background of this research is the decrease in the number of Umrah pilgrims departing with PT Asyesa Hasanah Tour & Travel SUMBAR Padang City both before and after the co-19 pandemic. From the results of data analysis, this study showed quite good results by analyzing the planning management carried out by PT Asyesa Hasanah Tour & Travel SUMBAR, Padang City before and after the Covid-19 pandemic and knowing the inhibiting factors in carrying out its planning management. There are changes in marketing strategies, products and services offered to attract Umrah pilgrims.